If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9 + 2(x + -7) = 9 + -9(x + -9) Reorder the terms: 9 + 2(-7 + x) = 9 + -9(x + -9) 9 + (-7 * 2 + x * 2) = 9 + -9(x + -9) 9 + (-14 + 2x) = 9 + -9(x + -9) Combine like terms: 9 + -14 = -5 -5 + 2x = 9 + -9(x + -9) Reorder the terms: -5 + 2x = 9 + -9(-9 + x) -5 + 2x = 9 + (-9 * -9 + x * -9) -5 + 2x = 9 + (81 + -9x) Combine like terms: 9 + 81 = 90 -5 + 2x = 90 + -9x Solving -5 + 2x = 90 + -9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '9x' to each side of the equation. -5 + 2x + 9x = 90 + -9x + 9x Combine like terms: 2x + 9x = 11x -5 + 11x = 90 + -9x + 9x Combine like terms: -9x + 9x = 0 -5 + 11x = 90 + 0 -5 + 11x = 90 Add '5' to each side of the equation. -5 + 5 + 11x = 90 + 5 Combine like terms: -5 + 5 = 0 0 + 11x = 90 + 5 11x = 90 + 5 Combine like terms: 90 + 5 = 95 11x = 95 Divide each side by '11'. x = 8.636363636 Simplifying x = 8.636363636
| 4(60+30x)+40+20x=470 | | 6+1.50(x)=16.50 | | (4x-1)=-21 | | 1/3(7x-2+3/4x) | | 2/7v=16 | | 60+30x+40+20x=470 | | 14-(2x+5)=-x+9 | | 7r-r=-5 | | 3+7x=11+9x | | 2x^3+6y^2=8x+24 | | 50=28.100.15m | | 4(2x+4)+5=20+8x | | -4m-12=24 | | 7/3x+63/84 | | 18+2g=30 | | 5(x+3)+10x+25(x+7)=390 | | 1470+7(x-30)=210 | | -4(5x+7)=-5 | | -64=-2x+4(x-21) | | x-10=2(x-4) | | 10.6-0.5a+1.4-1.4a=24-1.9a-4.3 | | 12x-3(3x+4)=6 | | 3(x+4)=18-x | | 16=86-29n | | 86-29x=16 | | 3x-3+10x+4=12 | | 1470+7(x-30)=60 | | 7/3x+63/84=20 | | (7t-21)+(r+4)=15 | | 5x+3y=9fory | | 5(3-x)-2(x-4)=15 | | 9(-5-6r)=5 |